LEARNING DIFFICULTIES OF PRIMARY SCHOOL PUPILS OCCURING DUE TO UNFAVOURABLE ENVIRONMENTAL FACTORS: THE EXPERIENCE OF TEACHERS - Raudeliunaite, Rita; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The objective of the study, which is presented in the article, is to identify learning difficulties of primary school pupils occurring due to unfavourable environmental factors on the basis of the experience of pedagogues. Problematic study question: What learning difficulties of pupils resulted in by unfavourable environmental factors do primary school teachers encounter? Qualitative research type was chosen for the study. In the study, the method of a semi-structured interview was used. The study data were processed by using the method of content analysis. 12 pedagogues participated in the study.The study findings revealed that primary school teachers encounter three different types of learning difficulties of pupils occurring due to unfavourable environmental factors: academic, social, behavioural and emotional.Academic difficulties should be associated with a reduced interest of children in their environment, the lack of knowledge and experience, the lack of curiosity and desire to learn something new, a lower level of preparedness for school, attention retention problems, passivity when performing tasks, distrust/doubts regarding his/her abilities, fluctuation, regress or stagnation of a child's progress (learning achievements), reduced interest in learning and poor learning efforts when performing tasks, the lack of learning motivation, getting late to classes or missing them.Social difficulties are associated to the lack of communication skills (contact establishment, politeness, attention when communicating with others, discipline, self-regulation, conflict resolution) and activity organisation and cooperation skills (ability to prepare tools for a specific activity, consistency when performing tasks; the performance of tasks to the end; the self-evaluation of activity results; involvement in a group activity; to listen to and hear what others say, consulting with others, permission to express their opinion give to others; ability to receive a different opinion and to express their opinion politely, avoidance to downgrade others, offering assistance to others and assistance solicitation, if need be; uttering compliments). The study revealed that primary school teachers also encounter with various behavioural and emotional difficulties.